Perception of Communication Student of State Islamic University of North Sumatera on COVID-19 News on the Ministry of Health of the Republic of Indonesia's Facebook Accounts - Muhammad Aidil Abror Nasution; Syukur Kholil (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
The purpose of this study is to discover how students perceive COVID-19 news on the Ministry of Health of the Republic of Indonesia's Facebook page (Kemenkes RI). The type of phenomenological theory is used as the theoretical basis in analyzing the problems in this qualitative research, namely researchers are required to obtain data and information through in-depth interviews and observations. The descriptive qualitative approach is used in this study. Informants in the study included two outstanding students who had sported the Department of Communication Science and the University's names, as well as three Communication Science students who led an organization on and off campus. Interviews, observation, and documentation were used to collect data from student informants at the State Islamic University of North Sumatra (UINSU) using a phenomenological study approach, in which the researcher attempted to find the meaning of the perception phenomenon experienced by the informant. The data analysis is descriptive, which means it summarizes all of the information gathered from the interviews. According to the findings of this study, many students value the Ministry of Health of the Republic of Indonesia's Facebook page (Kemenkes RI). Because having the news on the account will, of course, reduce the spread of fake news about COVUD-19 on Facebook social media.